A statistical approach for arsenic adsorption onto Turkey clinoptilolite - Simsek, E. Bilgin; Tuna, A. O. Avci; Beker, U. (SPRINGER HEIDELBERG, 2015)
The present study investigated the optimization of arsenic adsorption onto natural clinoptilolite (NC-Na). Response surface methodology in combination with Box-Behnken design was used to optimize the parameters of the adsorption process. Solution pH, temperature, and initial arsenic concentration were chosen as the main process variables, and the amount of arsenic adsorbed was selected as the investigated response. The analysis of variance results of the response surface model for arsenate (As(V)) adsorption on NC-Na showed that the effects and the interactions of pH and temperature were highly significant according to the p values (p < 0.05). The optimum conditions were found to be the solution pH of 5.0, temperature of 45 degrees C, and initial concentration of 7.8 mg L-1. The response surfaces derived from the models revealed that solution pH and temperature showed the greatest effect on the As(V) adsorption capacity of natural clinoptilolite.
Keywords: Clinoptilolite; Natural zeolite; Arsenic; Adsorption; Statistical design; Response surface methodology; Box-Behnken design; MODIFIED ZEOLITE; REMOVAL; AS(V); IRON; SORPTION; WATER; ADSORBENTS; Environmental Sciences & Ecology